Dinâmicas de integração no campo da saúde em cidades gêmeas do Paraná - Aikes, Solange (2017)
The present research deals with the cross-border processes in public health in the twin cities of Paraná: Foz do Iguaçu, Guaíra, Santo Antônio do Sudoeste and Barracão. Its objectives were: to understand the dynamics of access to cross-border health services in the view of key informants; To identify the integration strategies of the public health services used by technicians and managers of the twin cities of the state of Paraná and to analyze the treatment given to the topic of health in the border region in the regional cooperation agreements of Mercosur and Unasur. It was a descriptive, documentary and field research. For documentary research, documents produced by Mercosur and Unasul obtained from the official websites of these institutions were used as data sources. For field research, a semistructured instrument was used, applied to key informants. The empirical data analysis methodology was the thematic content analysis proposed by Bardin. The results are presented in the form of three articles that analyze the findings and discuss the most relevant issues. With the analysis of the Mercosur and Unasur documents, there was a difference between the objectives and the precepts that foment each one of the institutions. Although they do not have specific policies for border regions, regional integration processes that begin with trade and the economy must advance the social issue. For more than two decades, borders have been the subject of discussions in several technical groups, mainly related to health control and surveillance. However, there are no proposals for changes in legal provisions, nor the granting of autonomy to these populations. In the field research, it was verified that the official integration initiatives in the twin cities of Paraná, are also centered in the emergency perspective, related to sanitary and epidemiological surveillance in health. It was identified that vaccination is an offered service, without segregation. The lack of municipal autonomy to propose political changes, and especially the asymmetries of systems and structures, were pointed out as obstacles to integration. It was verified that there is no standard regarding access to health services in the twin cities, but there is a significant grant to the health professional of the selectivity of access to the public health system in relation to nonnationals. The lack of clarity regarding the access and interruption of care in the care network contravene guidelines present in the Unified Health System, fundamental for the realization of the right to health, integrality and universality. The findings found in the research, even with the inherent dynamics of these processes, were identified at other times mainly after the implementation of Sis-Fronteira, but the fact is that discrimination and obstacles to the realization of rights to the cross-border population still persist. Cross-border disorganization of concepts of nationality, citizenship and sovereignty, especially when related to the realization of social rights. There is a need for public policy discussions in South American countries that guarantee universal social rights and the creation of regional citizenships that portray the reality experienced by this population.